2014
DOI: 10.16970/ted.10646
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant toxicity and antiacetylcholinesterase activity of Saudi Mentha longifolia and Lavandula dentata species against Callosobruchus maculatus (F.) (Coleoptera: Bruchidae)

Abstract: Mentha longifolia (L.) and Lavandula dentata (L.) (Lamiaceae) are two wild growing folk medicine plants that in Saudi Arabia. This work was conducted to investigate the chemical composition and evaluate the fumigant toxicity of their essential oils against the adults (3-5-day-old) of cowpea beetle, Callosobruchus maculatus (F.) (Coleoptera: Bruchidae). The main compounds in M. longifolia oil were pulegone (74.95%), 1,8-cineole (7.35%), l-menthone (6.62%), and eucarvone (2.68%), while the main constituents in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
8
2
1
Order By: Relevance
“… Kumar et al (2009) reported that essential oil from Mentha species is very effective and completely inhibited oviposition of C. chinensis at 200 μl/l and protected seed (94.05%) from biodeterioration of C. chinensis . Against adults of C. maculatus, Mentha oil showed 4.43 μl/l air LC 50 values and at 1.01 μl/l air dose possessed anti acetylcholinesterase activity ( Al-Sarar et al, 2014 ).…”
Section: Biological Activity Of Essential Oils Of Mentha mentioning
confidence: 99%
“… Kumar et al (2009) reported that essential oil from Mentha species is very effective and completely inhibited oviposition of C. chinensis at 200 μl/l and protected seed (94.05%) from biodeterioration of C. chinensis . Against adults of C. maculatus, Mentha oil showed 4.43 μl/l air LC 50 values and at 1.01 μl/l air dose possessed anti acetylcholinesterase activity ( Al-Sarar et al, 2014 ).…”
Section: Biological Activity Of Essential Oils Of Mentha mentioning
confidence: 99%
“…Many reports published have shown lavender essential oil to possess high cholinesterase inhibitory activities [ 6 , 7 ] and other biological activities beneficial to human health, such as being antibacterial, antifungal [ 8 ], sedative [ 9 ], anti-depressive, effective for burns and insect bites [ 10 ], anticancer [ 11 ], anti-spasmolytic, anti-inflammatory [ 12 ], antioxidant [ 13 ], acaricides etc. [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The management of stored insect pests mostly relies on the use of synthetic insecticides such as deltamethrin, permethrin, pirimiphos-methyl, chlorpyrifos-methyl and fumigation with methyl bromide or phosphine (White & Leesch, 1995). Such treatments are simple and inexpensive, and even a single application of fumigation can control insect infestation for a substantial period (Daglish & Bengston, 1991;Alsarar et al, 2014). However, widespread use of these chemicals can lead to development of insect resistance (Waiss et al, 1981;Zettler & Cuperus, 1990;White, 1995;Tapondjou et al, 2002), health and environment hazards (Taylor, 1994;Prakash & Rao, 2006;Rahman et al, 2009), toxicity to non-target organisms, and pesticide residues inducing mutagenic and carcinogenic effects on human health (Lee et al, 2004;Isman, 2006).…”
Section: Introductionmentioning
confidence: 99%